Particle size selection device for use with the Turbohaler. Issue 5 (May 1996) - Everard, M. L.; Devadason, S. G.; Le Souef, P. N.
Abstract : BACKGROUND: Drug deposited within the upper airways of patients using dry powder inhalers does not contribute to the therapeutic effect but can result in unwanted local side effects and, when swallowed, may contribute to systemic effects. A chamber has been devised which uses the centrifugal force generated by the Turbohaler to remove large "non-respirable" particles with a view to minimising deposition in the upper airway. An in vitro study was performed to determine whether such a chamber could reduce the dose contained in coarse particles without having a significant effect on the "respirable dose". METHODS: The mouthpiece of a 200 micrograms Turbohaler was modified to allow a small volume chamber to be attached. The particle size distribution generated by the Turbohaler was assessed using a multi-stage liquid impinger with a flow rate of 60 l/min. The quantity of drug on each stage was quantified using an ultraviolet spectrophotometric technique. For each experiment 10 actuations were used to ensure adequate quantities of drug on each stage. Particles depositing on stages 3 + 4 have a diameter of < 6.8 microns and are arbitrarily referred to as the "respirable dose". The particle size distribution obtained using the Turbohaler (n = 10) was compared with that from the Turbohaler+ chamber (n = 11). RESULTS: The addition of the chamber resulted in the mean (SD) dose contained in larger "non-respirable" particles depositing on stages 1 + 2 being reduced from 52.2 (12.3) to 29.6 (6.9) micrograms per actuation. However, the chamber did not affect the "respirable" dose. The dose contained in particles with a diameter of < 6.8 microns from the standard Turbohaler was 91.1 (8.9) micrograms compared with 82.4 (18.6) micrograms when used with the chamber. CONCLUSIONS: These results indicate that it is possible to devise an effective particle size selection device for the Turbohaler. It may be possible to produce such devices for other dry powder inhalers, although the design would need to be tailored to each particular device.